A theoretical framework for mentor–protégé matchmaking: the role of mentoring in entrepreneurship. (1st January 2014) - Memon, Jamshed; Rozan, Mohd Zaidi Abd; Ismail, Kamariah; Uddin, Mueen; Balaid, Ali; Daud, Dzurllkanian
Entrepreneurial mentoring may not only help entrepreneurs to survive, but can also help them to avoid having to compromise their own responsibilities in a better and more sustainable environment, rather than simply pursuing a quest for profit. New start-ups will be more focused on using green technologies while developing their products at the same time. Research shows that such people are more inclined towards using greener products, provided the functionality and the price of the products are equivalent. This study proposes a theoretical framework for this purpose based on the theory of planned behaviour (TPB) and Social Exchange Theory (SET). Integration of these theories will help explain why entrepreneurs want to be mentored, who influenced their intentions towards mentoring, what their preference is, in selecting a mentor, and what factors affect their relationship with a mentor. This conceptual model will help in the matchmaking of the right mentor with the right protégé.